Prevalence, Awareness, Treatment, and Control of Hypertension in Young Adults (20–39 Years) in Kerala, South India - Geevar, Zachariah; Krishnan, Mangalath Narayanan; Venugopal, Krishnannair; Sanjay, Ganesh; Harikrishnan, S.; Mohanan, Padinhare Purayil; Mini, G. K.; Thankappan, Kavumpurathu Raman (Frontiers in Cardiovascular Medicine, 2022)
Prevalence, awareness, treatment and control of hypertension in young adults (20 to 39 years) in Kerala, South India Abstract Objective: We sought to study the prevalence of hypertension and the levels of awareness, treatment and control of hypertension in the young adults in Kerala, India compared to older adults. Methods: We identified 1221 young adults (men 36.7%) in the age group 20 to 39 years from the 5150 participants of the Cardiological Society of India Kerala Coronary artery disease (CAD) and its Risk factors Prevalence (CSI Kerala CRP) Study. We determined prevalence and levels of awareness, treatment and control of hypertension and compared to older adults Results: We found that among the young adults, 11.2% had hypertension and 33.3% had prehypertension. Hypertension was nearly three times more prevalent among men than women (20.5% vs 7.5% p <0.001) while in older adults there was no difference between men and women in its prevalence. Male sex (OR 3.36, 95% CI 2.15-5.25 p value < 0.001), urban residence (OR 2.21, 95% CI 1.52-3.22 p value < 0.001), abdominal obesity (OR 1.74, 95% CI 1.06-2.87 p value 0.028) and hypercholesterolemia (OR 1.64 95% CI 1.12-2.40 p value 0.011) were significant factors favouring hypertension in the young adults. Awareness and treatment of hypertension were significantly poor among younger adults compared to older adults. In young adults, awareness, treatment and control of hypertension were significantly lower among men compared to women. (23.9% vs 51.7% p 0.001, 12.0% vs 25.9% p 0.045, and 18.5% vs 37.9% p 0.012 respectively). Participants who had checked blood pressure at least once during the previous year had significantly better awareness and treatment (58.7% vs 24.0% and 41.3% vs 19.2% respectively). Conclusions: We found that one eighth of young subjects had hypertension with three times higher prevalence of hypertension among men compared to women. Awareness, treatment and control of hypertension were less among young adults and worse in young men compared to young women. Identifying hypertension and measures to control it are important and should be specifically targeted to young men